Modeling the Phenotypic Characteristics of Pinus Brutia Trees in Northern Iraq - Ahmed, Abubaker Jasim; A. J. M., Al-Yousif (American Journal of Botany and Bioengineering, 2025)
The morphological characteristics of forest trees are fundamental factors influencing their growth dynamics and overall development. These traits play a crucial role in evaluating biological productivity and understanding growth patterns within forest ecosystems. Mathematical modeling serves as an essential tool for analyzing changes in tree volume and biomass. In this study, 26 circular sample plots, each with a radius of 17.9 meters, were established in naturally growing Pinus brutia stands located in the Dohuk region of northern Iraq. Field data were collected from each plot, including diameter at breast height (DBH), total tree height, crown height, crown length, and crown center height. Additional calculations included basal area, crown coverage area, volume, and annual increments in diameter, height, and volume. Using these data, a variety of regression models were employed to develop equations estimating the annual growth in diameter, height, and volume. Model selection was based on several statistical criteria, including the coefficient of determination (R²), standard error of the parameters, the Durbin-Watson statistic, and residual analysis. These indicators confirmed the accuracy and reliability of the developed models. Based on the results, growth tables were constructed to illustrate changes in diameter and height across two consecutive periods relative to tree height.